Fasting blood glucose-to-glycated hemoglobin ratio for evaluating clinical outcomes in patients with ischemic stroke - Shao, Tengfei; Liu, Hui; Yang, Guochao; Wang, Huan; Li, Di; Ni, Huanyu; Xu, Yun; Zhang, Jinping (Frontiers in Neurology, 2023)
Background Stress hyperglycemia frequently occurs in acute ischemic stroke (AIS). The influence of stress hyperglycemia to outcomes of AIS patients remains ambiguous. Methods Data from our institution of patients with AIS between June 2020 and June 2021 were retrospectively analyzed. The severity of stroke was assessed at admission with the National Institutes of Health Stroke Scale (NIHSS) and primary endpoint was functional outcomes. Stress hyperglycemia was measured by glucose-to-HbA1c ratio. Two models that retained or excluded the NIHSS in the multivariable analysis were adopted to explore the relationship between stress hyperglycemia and outcomes. Receiver operating characteristic curve (ROC) was calculated to determine an optimized cut-off value. Results The optimal cut-off was 1.135. When all patients including, model 1 didn’t find the relationship between glucose-to-HbA1c ratio and functional outcomes. In model 2, glucose-to-HbA1c ratio×10(glucose-to-HbA1c ratio×10) was the independent predictor of functional outcomes (OR 1.19, 95% CI 1.07–1.33, p< 0.01). Separately, in patients without diabetes, glucose-to-HbA1c ratio×10 was the independent predictor of functional outcomes in both Model 1 (OR 1.37, 95% CI 1.08–1.73, p=0.01) and Model 2 (OR 1.48, 95% CI 1.22–1.79, p<0.01) while not in patients with diabetes. What’s more, glucose-to-HbA1c ratio×10 was the independent predictor of the stroke severity (OR 1.16, 95% CI 1.05–1.28, p<0.01). Conclusion The glucose-to-HbA1c ratio was associated with more severe AIS. Specifically, glucose-to-HbA1c ratio was associated with functional outcomes in patients without diabetes, not in patients with diabetes.